Impact of Employee Motivation on Organizational Effectiveness in Nepalese Organizations - Bhandari, Yashna (Nepalese Journal of Management, 2024)
This study examines the impact of employee motivation on organizational effectiveness in the context of Nepalese organizations. Organizational productivity and motivation are the dependent variables. Likewise, the selected independent variables are salary, promotion, performance appraisal, training and development, job security and health benefit facilities. The primary source of data is used to assess the opinions of the employees regarding salary, promotion, performance appraisal, training and development, job security and health benefit facilities in Nepalese financial institutions. The study is based on primary data with 140 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of employee motivation and its impact on organizational effectiveness in Nepalese organizations. The study showed that salary has a positive impact on employee motivation and organizational productivity. It implies that increase in salary leads to increase in employee motivation and organizational productivity. The result also showed that promotion has a positive impact on employee motivation and organizational productivity. It implies that increase in promotion opportunities leads to increase in employee motivation and organizational productivity. Moreover, performance appraisal system has a positive impact on employee motivation and organizational productivity. It implies that better performance appraisal system leads to increase in employee motivation and organizational productivity. Furthermore, job security has a positive impact on employee motivation and organizational productivity indicating that increase in level of job security leads to increase in employee motivation and organizational productivity. Similarly, the result also showed that training and development has a positive impact on employee motivation and organizational productivity. It indicates that better training and development leads to increase in employee motivation and organizational productivity. The result also showed that health benefit has a positive impact on employee motivation and organizational productivity. It implies that increase in health benefits leads to increase in employee motivation and organizational productivity.